A STUDY OF JARGON USED ON FOOD & BEVERAGE DIVISION AT THE ALIMAR PREMIER HOTEL SURABAYA - Budianto, Suhartawan; Pramesti, Mutiara Widya Noor (Faculty of Letters, Dr. Soetomo University, 2016)
This research focuses on study of the forms of jargon and functions that used by foodandbeveragedivisionatTheAlimarPremierHotelSurabaya.The study writer uses the theory of sociolinguisticsby Chaer (1994) to answer the language varities in the form of jargon and also the theory of function of jargon by Ives (1999) that used by the employeesin the food and beverage division at The Alimar Premier Hotel Surabaya. This study uses qualitative method to analyze the jargon. The aim ofqualitativemethoditselfistoobtainsystematicallydescriptionandaccuratefacts. It concerns with the collected data that often uses words. To collect the data, the first step that the thesis writer used was recording some conversations between the employees in thesame division. After recording the conversations, the thesis writer transcribes the data into a table and classifies what are the inventions of the language varities in the form of jargon shich is found inthe conversation. After analyzing the data, the jargon that usually spoken by the employees in the food and beverage division are in the form words and phrases. By using jargon to explain somethingtothesamedivision,theyareabletospeakusingmorelanguagevarieties